Motion compensation for unmanned aerial vehicle's synthetic aperture radar - Labowski, Michal; Kaniewski, Piotr (2015 Signal Processing Symposium (SPSympo), 2015)
The paper presents a method of calculation of motion correction parameters for a Synthetic Aperture Radar (SAR) installed on an Unmanned Aerial Vehicle (UAV). The UAV on-board system consists of a Radar Sensor, an Antenna System, a SAR Processor and a Navigation System. The main task of the navigation part is to determine the vector of difference between a theoretical and a real trajectory of the UAV's center of gravity. The paper includes chosen results of experiments obtained during ground tests.